Six Palmyrene Portraits Destroyed in Manbij, Syria: A Salvage Reading - Hutton, Jeremy M. (Bulletin of ASOR, 2017)
Operatives of the Islamic State reportedly destroyed six Palmyrene funerary busts and statue fragments in Manbij, Syria, on July 2, 2015. This article considers the ethical implications of publishing photographs of antiquities that have been destroyed, arguing that in such dramatic cases as destruction, it is justified to publish readings. Photographs of these antiquities are then analyzed, their physical and iconographic characteristics described, and readings for three of the inscriptions suggested. Finally, the loss of data caused by the items' destruction is measured against the loss of data occasioned by looting.